Positive Inotropic Effect of Rosiglitazone in Papillary Muscles in Control and Diabetic Rats - Kavak, Servet; Emre, Mustafa; Bozkurt, Abdi; Demir, Halit (Asian Journal of Chemistry, 2010)
Peroxisome proliferator-activated receptor γ activators or rosiglitazone (RSG) used as insulin sensitizers in the treatment of diabetes. The aim of this study is the effects of RSG on papillary muscle positive inotropic were studied in left ventricular papillary muscles from both control rats and rats diabetes. In this study, we used four groups: (1) untreated control (C) (2) rosiglitazone-treated control (C + RSG), (3) diabetes (D) and (4) rosiglitazone-treated diabetes groups (D + RSG). Diabetes was induced by a single intraperitoneal injection of streptozotocin (STZ) for 8 weeks STZ-treatment (STZ, 45 mg/kg). Papillary muscle from spontaneously diabetic hearts exhibited a depressed conraction force (CF), prolonged contraction time (CT) and half relaxation time (1/2 RT) and reduced contraction and relaxation velocities (± dp/dt) (p < 0.05). It is found that the lipid profile and glycohemoglobin levels (HbA1c) levels in D + RSG group as it increase the C rats value at the end of the treatment period (p < 0.05). D + RSG and C + RSG groups exhibited a increased CF, shortened CT and 1/2 RT and increased ± dp/dt (p < 0.05). Treatment of rats with RSG also markedly decreased the insulin resistance of the hearts. Present data suggest that the beneficial effects of RSG treatment on the mechanical activities of the diabetic rat papillary appear to be due to the restoration of the diminished SR Ca2+ release triggering, partially, related to the restoration of the hyperglycemia.